2006
DOI: 10.1002/ange.200503975
|View full text |Cite
|
Sign up to set email alerts
|

Ein ungesättigtes α,ω‐dianionisches Oligosilan

Abstract: Ein α,ω‐dianionisches Trisilen wurde durch Reduktion von Dichlortrisilen 1 mit aktivem Magnesium hergestellt. Das Trisilendiid 2 wurde durch NMR‐Spektroskopie und Kristallstrukturanalyse charakterisiert. Sein Potenzial als Ausgangsverbindung in der Synthese von Heterocyclen mit Si‐Si‐Doppelbindung wird durch die Bildung des Stannatrisilacyclobutens 3 aus 2 und Me2SnCl2 betont.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 46 publications
0
6
0
1
Order By: Relevance
“…On the basis of the successful synthesis of 3, we concluded that 8 might occur as an intermediate of the previously reported synthesis of the magnesium salt of a trisilendiide 9. [19] Indeed, the use of Et 2 O as a solvent instead of THF during the reduction of the dichlorosilyl disilene precursor with magnesium powder halts the reaction at the stage of neutral species 8 (Scheme 5). Cyclotrisilene 8 was isolated as orange crystals from a concentrated pentane solution in 51 % yield (mp.…”
Section: Dedicated To Prof Theophil Eicher On Occasion Of His 80th Bmentioning
confidence: 99%
“…On the basis of the successful synthesis of 3, we concluded that 8 might occur as an intermediate of the previously reported synthesis of the magnesium salt of a trisilendiide 9. [19] Indeed, the use of Et 2 O as a solvent instead of THF during the reduction of the dichlorosilyl disilene precursor with magnesium powder halts the reaction at the stage of neutral species 8 (Scheme 5). Cyclotrisilene 8 was isolated as orange crystals from a concentrated pentane solution in 51 % yield (mp.…”
Section: Dedicated To Prof Theophil Eicher On Occasion Of His 80th Bmentioning
confidence: 99%
“…In 2006, Scheschkewitz et al reported the syntheses andi solation of the first a,w-dianionic unsaturated oligosilane (Scheme 19). [52] The treatment of cyclotrisilene 57 d with an excess of Bogdanovic magnesium [53] in THF affords the magnesium salt of trisilendiide 58,w hich was isolated as very air-sensitive,b ut thermally highly stable( M.p. 2098)o rangec rystals.…”
Section: Reactionsofc Hlorosilyl-substituted Disilenesmentioning
confidence: 99%
“…In a transmetalation reaction of 58 with Me 2 SnCl 2 in [D 6 ]benzene, the corresponding tin derivative 59 is formed, which was characterizedb ymultinuclear NMR spectroscopy (Scheme 19). [52]…”
Section: Reactionsofc Hlorosilyl-substituted Disilenesmentioning
confidence: 99%
See 1 more Smart Citation
“…Diesem Schritt schließt sich die cyclische Umlagerung der Elektronen im Si 3 -Fragment und die ¾nderung des Koordinationsmodus des Cp*-Systems an. [19] In der Tat hält der Einsatz von Et 2 O als Lçsungsmittel anstelle von THF während der Reduktion der Dichlorosilyldisilenvorstufe mit Magnesiumpulver die Reaktion auf der Stufe des neutralen 8 an (Schema 5). Anscheinend erzeugen konkurrierende Elektronentransferprozesse radikalische Fragmente, die anschließend homokuppeln.…”
Section: Die Bildung Von 3 Kann Leicht Durch Einen Intramolekularenunclassified